THE EFFECTS OF GRANTING STUDENTS SCHOLARSHIPS ON THE LEARNING MOTIVATION OF THE STUDENTS OF THE ECONOMICS FACULTY OF YOGYAKARTA STATE UNIVERSITY IN 2012 - Danang Waskito; Kholifatun Azizah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
in nature. Questionnaires were distributed to the studentsawarded scholarships in the Economics Faculty of Yogyakarta State University in2012. The students of the Economics Faculty awarded scholarships served as thesample of the research. The students of the Economics Faculty of Yogyakarta StateUniversity were the population of the research. The proportional random samplingwas the sampling technique used and the result were 32 respondents who were thestudents awarded the Bidik Misi scholarship, 1 respondent who was awarded theSupersemar scholarship, 21 respondents who were awarded PPA scholarship, 21respondents who were awarded the BBM scholarship, 1 respondent who wasawarded the BI scholarship, and 1 respondent who was awarded the BNI scholarship.The findings showed that granting scholarships affected the students’ learningmotivation as much as 7.4%. Meanwhile, 92.6% of the students’ learning motivationdepended on other variables not studied by the researcher. The significance level ofthe students awarded the Bidik Misi scholarship was 0.000 0.005, whereas that ofthe students awarded other scholarships was 0.000 0.005. It means there is adifference between the tow of them. There was a difference in the learning motivationbetween the students awarded the Bidik Misi scholarship and those who wereawarded other scholarships.